Overcoming Psychological Disorders Through Spiritual Guidance for Muslim Felons - Afrinaldi Afrinaldi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This study aims to describe, first: the psychological disorders of Muslim inmates who experience trauma as a result of not being ready to accept the reality of serving time as convicts in prison. Psychological disorders are in the form of behavior: difficulty controlling emotions, disappointment, sadness, blaming others, difficulty managing stress, difficulty controlling oneself, feelings of guilt, anxiety, and depression. Second: spiritual development by Correctional Institution (LP) officers through mental coaching in the form of routine activities such as carrying out congregational prayers, sermon training, giving speeches, and reading and understanding the contents of the Koran. Mental development aims to open oneself and foster a strong religious attitude in order to accept divine destiny with patience and trust. This self-awareness becomes positive energy to stimulate spiritual potential to shape self-character to become a pious person individually and socially. A qualitative descriptive approach was chosen to gather information from informants through non-participant observation and in-depth interviews (in-depth interviews). The collected data is reduced, displayed, verified and analyzed and constructed into a new concept. The research findings found that immoral informants (drug cases, murder, theft, and corruption) were dominantly experiencing psychological disorders compared to immoral informants (rape cases). It is easier for immoral informants to open up and be actively involved in participating in mental coaching activities, while immoral informants still find it difficult to accept the reality of life so they are more withdrawn and choose not to take part in mental coaching activities. Strengthening spirituality that is dynamic and innovative as well as rich in new methods is expected to be the right solution for the recovery of psychological disorders of Muslim inmates while in prison